Burning the candle at both ends: Intraretinal signaling of intrinsically photosensitive retinal ganglion cells - Raja, Sushmitha; Milosavljevic, Nina; Allen, Annette E.; Cameron, Morven A. (Frontiers in Cellular Neuroscience, 2023)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) are photoreceptors located in the ganglion cell layer. They project to brain regions involved in predominately non-image-forming functions including entrainment of circadian rhythms, control of the pupil light reflex, and modulation of mood and behaviour. In addition to possessing intrinsic photosensitivity via the photopigment melanopsin, these cells receive inputs originating in rods and cones. While most research in the last two decades has focused on the downstream influence of ipRGC signalling, recent studies have shown that ipRGCs also act retrogradely within the retina itself as intraretinal signalling neurons. In this article, we review studies examining intraretinal and, in addition, intraocular signalling pathways of ipRGCs. Through these pathways, ipRGCs regulate inner and outer retinal circuitry through both chemical and electrical synapses, modulate the outputs of ganglion cells (both ipRGCs and non-ipRGCs), and influence arrangement of the correct retinal circuitry and vasculature during development. These data suggest that ipRGC function plays a significant role in the processing of image-forming vision at its earliest stage, positioning these photoreceptors to exert a vital role in perceptual vision. This research will have important implications for lighting design to optimise the best chromatic lighting environments for humans, both in adults and potentially even during foetal and postnatal development. Further studies into these unique ipRGC signalling pathways could also lead to a better understanding of the development of ocular dysfunctions such as myopia.